Cundinamarca Department revenues and their behavior (2014)
According to the “Estatuto de Rentas de Cundinamarca” there are essential constitutional values of taxation that corresponds to due process, tax equity, efficiency, escalation and rents autonomy which benefit to the Nation, to the Departments and to the taxpayers. It ́s necessary to have into account that this one is based on legal principles of equality, fairness, good faith, morality, participation, responsibility, clarity, advertising, coordination, efficiency, economy, speed and legality.